Romania on the diplomatic and planning agenda of Britain and U.S.A. during the Second World War (1940-1944) - Dan Dragoş Sichigea (Codrul Cosminului, 2013)
The Second World War was arguably the most important event that shaped the world in the last century. Without a doubt it marked a significant change in the way we see and interpret international relations because it brought into question a new word a status of strength: the superpowers. Even during the war it became apparent that the new world emerging from the conflict will be dominated by the U.S.A and the Soviet Union. For the subject at hand here – Romania and its relations with the West at the time, Russian vicinity is a very determining factor. The way Britain and its bigger partner, the U.S. viewed Romania during those troubled years was unquestionably altered by Russian influence. This fact remained unchanged, even though there were some elements that may suggest otherwise. Especially the British started to think of Romania as a future battlefield and didn’t ignore its strategic importance when they started postwar planning procedures. This paper focuses on the place occupied by Romania in the Allied plans and predictions, especially in the bigger of picture, which included the Soviet Union.